Sex Differences in Coronary Microvascular Function in Individuals With Type 2 Diabetes - Andrea Haas; Bernard Rosner; Raymond Y. Kwong; A.D. Rao; Rajesh Garg; Marcelo F. Di Carli; Gail K. Adler (2018)
Cardiovascular (CV) disease fatality rates are higher for women compared with men with diabetes despite lower rates of obstructive coronary artery disease (CAD). Impaired coronary flow reserve (CFR), the ratio of adenosine-stimulated to rest myocardial blood flow (MBF), is an indicator of coronary microvascular dysfunction and predicts major adverse CV events. We performed a post hoc analysis to determine whether there was a sex disparity in coronary microvascular dysfunction among 46 men and 27 women with well-controlled type 2 diabetes and without clinical evidence of obstructive CAD. We found that women had a higher rest MBF, lower CFR, and worse diastolic function compared with men. In addition, rest MBF was positively correlated with worse diastolic function in women. We previously showed that mineralocorticoid blockade improved CFR in men and women with type 2 diabetes, implicating aldosterone in the pathophysiology of coronary microvascular dysfunction. We therefore examined aldosterone levels and found that women had larger increases in aldosterone in response to an angiotensin-II infusion than did men. In conclusion, among individuals with type 2 diabetes and good cardiometabolic control, women had worse myocardial perfusion and diastolic function compared with men. The greater aldosterone responsivity in women may be a mechanism for this sex effect.